The Tension between Due Process of Law and Counter-Terrorist Measures During the Initial Stages of Criminal Procedure - Ezioni, Limor (Bergen Journal of Criminal Law & Criminal Justice, 2014)
This article addresses the way the Israeli criminal system uses secret evidence during the initial stages of criminal procedure. In particular, the article discusses whether terror suspects should enjoy the same criminal procedure as regular criminal suspects, or whether the procedure should differ. The article identifies the underlying theories which guide the criminal justice system and applies them to Israeli criminal procedure with regards to privileged evidence. The article reviews how comparative law has approached the issue of secret evidence when it comes to terror suspects, and finally, discusses Israel’s Counter Terrorism Memorandum Bill.